Peptide microarray patterning for controlling and monitoring cell growth. (1st April 2016) - Lin, Edith; Sikand, Adhirath; Wickware, Jessica; Hao, Yubin; Derda, Ratmir
Graphical abstract: Abstract: The fate of cells is influenced by their microenvironment and many cell types undergo differentiation when stimulated by extracellular cues, such as soluble growth factors and the insoluble extracellular matrix (ECM). Stimulating differentiation by insoluble or "immobilized" cues is a particularly attractive method because it allows for the induction of differentiation in a spatially-defined cohort of cells within a larger subpopulation. To improve the design of de novo screening of such insoluble factors, we describe a methodology for producing high-density peptide microarrays suitable for extended cell culture and fluorescence microscopy. As a model, we used a murine mammary gland cell line (NMuMG) that undergoes epithelial to mesenchymal transition (EMT) in response to soluble transforming growth factor beta (TGF-β) and surface-immobilized peptides that target TGF-β receptors (TGFβRI/II). We repurposed a well-established DNA microarray printing technique to produce arrays of micropatterned surfaces that displayed TGFβRI/II-binding peptides and integrin binding peptides. Upon long-term culture on these arrays, only NMuMG cells residing on EMT-stimulating areas exhibited growth arrest and decreased E-cadherin expression. We believe that the methodology created in this report will aid the development of peptide-decorated surfaces that can locally stimulate defined cell surface receptors and control EMT and other well-characterized differentiation events. Statement of Significance: Scope of work: This manuscript aims to accelerate the development of instructive biomaterials decorated with specific ligands that target cell-surface receptors and induce specific differentiation of cells upon contact. These materials can be used for practical applications, such as fabricating synthetic materials for large scale, stem cell culture, or investigating differentiation and asymmetric division in stem cells. Specifically, in this manuscript, we repurposed a DNA microarray printer to produce microarrays of peptide-terminated self-assembled monolayers (SAMs). To demonstrate the utility of these arrays in phenotypic assays with mammalian cells, we monitored the induction of epithelial to mesenchymal transition (EMT) in murine mammary epithelial cells using specific peptide ligands printed on these arrays. Novelty: We, and others, have published several strategies for producing peptide-based arrays suitable for long-term phenotypic assays. Many reports relied on patterning steps that made adaptation difficult. The use of a DNA microarray printer as the sole production tool simplified the production of peptide microarrays and increased the throughput of this technology. We confirmed that simplification in production did not compromise the performance of the array; it is still possible to study short-term adhesion, long-term growth, and complex phenotypic responses, such as EMT, in the cells. EMT was studied using immunofluorescent staining after four days of culture. Impact: This methodology will serve as a foundation for future screening of instructive biomaterials in our research group. As DNA printers are broadly available in academic institutions, we foresee rapid adaptation of this approach by academic researchers.